In vitro safety and functional characterization of the novel Bacillus coagulans strain CGI314 - Mazhar, Shahneela; Simon, Annie; Khokhlova, Ekaterina; Colom, Joan; Leeuwendaal, Natasha; Deaton, John; Rea, Kieran (Frontiers in Microbiology, 2024)
Bacillus coagulans species have garnered much interest in health-related functional food research owing to their desirable probiotic properties, including pathogen exclusion, antioxidant, antimicrobial, immunomodulatory and food fermentation capabilities coupled with their tolerance of extreme environments (pH, temperature, gastric and bile acid resistance) and stability due to their endosporulation ability. In this study, the novel strain Bacillus coagulans CGI314 was assessed for safety, and functional probiotic attributes including resistance to heat, gastric acid and bile salts, the ability to adhere to intestinal cells, aggregation properties, the ability to suppress the growth of human pathogens, enzymatic profile, antioxidant capacity using biochemical and cell-based methods, cholesterol assimilation, anti-inflammatory activity, and attenuation of hydrogen peroxide (H2O2)induced disruption of the intestinal-epithelial barrier. B. coagulans CGI314 spores display resistance to high temperatures (40℃, 70℃ and 90℃), and gastric and bile acids (pH 3.0 and bile salt (0.3%)), demonstrating its ability to survive and remain viable under gastrointestinal conditions. Spores and the vegetative form of this strain were able to adhere to a mucous-producing intestinal cell line, demonstrated moderate auto-aggregation properties, and could co-aggregate with potentially pathogenic bacteria. Vegetative cells attenuated LPS-induced pro-inflammatory cytokine gene expression in HT-29 intestinal cell lines and demonstrated broad antagonistic activity toward numerous urinary tract, intestinal, oral, and skin pathogens. Metabolomic profiling demonstrated its ability to synthesize several amino acids, vitamins and short-chain fatty acids from the breakdown of complex molecules or by de novo synthesis. Additionally, B. coagulans CGI314's strong antioxidant capacity was demonstrated using enzyme-based methods and was further supported by its cytoprotective and antioxidant effects in HepG2 and HT-29 cell lines. Furthermore, B. coagulans CGI314 significantly increased the expression of tight junction proteins and partially ameliorated the detrimental effects of H2O2 induced intestinal-epithelial barrier integrity. Taken together these beneficial functional properties provide strong evidence for B. coagulans CGI314 as a promising potential probiotic candidate in food products.